2022
DOI: 10.1002/adem.202200641
|View full text |Cite
|
Sign up to set email alerts
|

Binder Jet 3D Printing of 316L Stainless Steel: Orthogonal Printing and Sintering Process Optimization

Abstract: Binder jet 3D printing (BJ3DP) is an additive manufacturing technique that uses a liquid binder to selectively deposit powder layer by layer to fabricate 3D parts followed by sintering. Herein, the printing parameters, sintering temperature, and holding time of 316L stainless steel (SS) materials produced by BJ3DP technique are systematically investigated. Based on the L9 orthogonal experimental design, the green parts can achieve the highest relative density of ≈55.9%, when the layer thickness, binder saturat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Nanolithography is a powerful technique, which enables the production of particles possessing very complex morphologies, with relative ease and high precision. [ 285 , 286 ] Nanolithography is one of the main methods of producing metamaterials, [ 285 , 287 ] to which most of the ML-based studies on chiral materials are devoted. These studies mainly use computer-simulated data, without resorting to the fabrication of real materials, but optimized structures can be easily discovered and subsequently fabricated by nanolithography.…”
Section: Chiral Nanomaterialsmentioning
confidence: 99%
“…Nanolithography is a powerful technique, which enables the production of particles possessing very complex morphologies, with relative ease and high precision. [ 285 , 286 ] Nanolithography is one of the main methods of producing metamaterials, [ 285 , 287 ] to which most of the ML-based studies on chiral materials are devoted. These studies mainly use computer-simulated data, without resorting to the fabrication of real materials, but optimized structures can be easily discovered and subsequently fabricated by nanolithography.…”
Section: Chiral Nanomaterialsmentioning
confidence: 99%
“…It can be observed that the sintered sample contains two phases, γ-austenite (γ-Fe) and δ-ferrite (δ-Fe) phase, which is consistent with EDS elemental analysis. [29] This is due to the fact that during the sintering process, the austenite promoting elements (usually Ni and C) diffuse within the γ-Fe matrix, and the ferrite promoting elements (usually Cr and Mo) diffuse at grain borders. The peak positions remain basically the same at different sintering temperatures.…”
Section: Chemical Composition Analysismentioning
confidence: 99%
“…In recent years, additive manufacturing (AM, also known as 3D-printing) has become a popular technique to manufacture products made of stainless steels due to its high speed and low cost. [3][4][5] AM also offers good properties such as generating less waste and being more flexible in producing complex parts. Among the AM techniques, the laser powder bed fusion (LPBF) is mostly used for processing 316L SS products.…”
Section: Introductionmentioning
confidence: 99%